Implementation of Group Counseling and Role-Playing: The Investigation of Students Social Interaction Improvement - Subandi, Subandi; Hasanah, Ida Faridatul; Dewi, Laila Ludfiana; Jannah, Siti Roudlotul (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
The authors found many students with low social interaction at school and lack of methods in anticipating this problem. This article contributes to providing alternative methods for enhancing students' social interaction by using role-playing techniques in group counseling. The purpose of this study is to determine the effectiveness of the role-playing technique in improving the social interaction of 8th-grade students at Public Junior High School 7 Bandar Lampung. The authors use social interaction scales to collect data and quasi-experimental research design methods. The subjects of the study were 16 students of 8th-grade Public Junior High School 7 Bandar Lampung which selected by purposive sampling. Data analysed using Wilcoxon Test. The results of the study concluded that z=-2.524 and p<0.05. This means that group counseling services with role-playing techniques are effective to improve social interaction for 8th-grade students at Public Junior High School 7 Bandar Lampung.